2020
DOI: 10.2147/cmar.s232235
|View full text |Cite
|
Sign up to set email alerts
|

<p>Circular RNA HIPK3 Promotes EMT of Cervical Cancer Through Sponging miR-338-3p to Up-Regulate HIF-1α</p>

Abstract: Background: Cervical cancer (CC) is the 4th most common malignancy and cancer-related fatality in women worldwide. Circular RNA is a newly recognized noncoding RNA form. More reports have confirmed their important regulatory functions in diverse physiological and cancer processes. However, the function and mechanisms of circ-HIPK3 in CC remain unknown. Methods: circ-HIPK3 expression status was verified between 45 paired CC and normal adjacent tissues from 45 CC patients, also the 6 CC cell lines and a normal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 35 publications
0
38
0
Order By: Relevance
“…CircCLK3 induces the levels of FOXM1 via sponging miR-320a, and overexpression of FOXM1 could trigger EMT-like changes, including the acquisition of Vimentin and N-cadherin expression and reduction of E-cadherin expression [99]. Also, the upregulation of circ0067934, circ0000745, ciRS-7 and circHIPK3 in CC cells was shown to increase the expression of mesenchymal markers and decrease the expression of epithelial markers [80,89,100,104]. Inactivation of p53 in human tumors occurs through missense mutations in the DNA-binding domain of the p53 protein, and can also result from the amplification/overexpression of its specific inhibitors (such as MDM2 and MDM4) [112].…”
Section: Circrnas In CCmentioning
confidence: 98%
See 2 more Smart Citations
“…CircCLK3 induces the levels of FOXM1 via sponging miR-320a, and overexpression of FOXM1 could trigger EMT-like changes, including the acquisition of Vimentin and N-cadherin expression and reduction of E-cadherin expression [99]. Also, the upregulation of circ0067934, circ0000745, ciRS-7 and circHIPK3 in CC cells was shown to increase the expression of mesenchymal markers and decrease the expression of epithelial markers [80,89,100,104]. Inactivation of p53 in human tumors occurs through missense mutations in the DNA-binding domain of the p53 protein, and can also result from the amplification/overexpression of its specific inhibitors (such as MDM2 and MDM4) [112].…”
Section: Circrnas In CCmentioning
confidence: 98%
“…Epithelial-mesenchymal transition (EMT) is a biological process in which epithelial cells acquire mesenchymal phenotypes, thus conferring the malignant properties to cancer cells including invasive behaviors, cancer stem cell properties, and greater resistance to cancer treatment [110]. Experimental studies have revealed that circRNAs affect the EMT program in human cancers (including CC) through different mechanisms [77,80,89,99,100,104,111]. For instance, circ000284 indirectly increases Snail-2 expression to promote EMT and invasion of CC cells through sponging miR-506 [77].…”
Section: Circrnas In CCmentioning
confidence: 99%
See 1 more Smart Citation
“…circRNAs act as important roles in the development and progression of cancers and are involved in various biological processes, such as cell proliferation, apoptosis, and migration by regulating gene expression ( Liu et al, 2019 ; Di Agostino et al, 2020 ; Ji et al, 2020 ; Tang and Chen, 2020 ; Wang et al, 2020c ). Mangy circRNAs have been reported to play important functions in cervical cancers, such as hsa_circ_0000515 ( Tang and Chen, 2020 ), has_ circ_0000388 ( Meng et al, 2020 ), circ-HIPK3 ( Qian and Huang, 2020 ), circ-ITCH ( Li et al, 2020 ; Wu et al, 2020b ), circCLK3 ( Jin et al, 2020 ), etc. However, the role and mechanism of circAMOTL1 in the cervical cancer are thoroughly unclear.…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs have been studied in a variety of human tumor types, including those affecting the reproductive and urinary systems, digestive system, nervous system, respiratory system, etc. (17)(18)(19)(20)(21). Currently, the enormous potential for circRNA use in targeted therapy and as a noninvasive biomarker has garnered much attention from the broader scientific community (22).…”
Section: Circrna and Cancermentioning
confidence: 99%